The Influence of Disaster Counseling with Animation Video on Preparednes Students in Elementary School in Palu (Medico Legal Update, 2020)
Background: The Central Sulawesi region is one of the areas prone to earthquakes and tsunamis in Indonesia. The low level of knowledge of the community, especially children who are the age most vulnerable to the risk of victims in a disaster. The vulnerability of children to disasters is triggered by a limited understanding of the risks around them, which results in the absence of preparedness in the face of disasters. This study aims to know the influences of disaster counseling with animation video on preparedness students in elementary school in sigi district.Methods: This research used a quasi-experimental with the pretest-posttest design. 40 respondents, grade IV and V student, were determined by the total quota sampling technique. Data was collected using questionnaires and observation sheets. Data analysis using t-dependent and will be presented in tabular form.Results: Shows that the average value of respondents’ knowledge before video playback (pre-test) is 83.12. Meanwhile, the average value after playing the video (post test) is equal to 92.62. This shows that an increase in the average value of respondents after the video playback. The results of the t-dependent test showed that the animation video method had a significant influence on improving preparedness (p = 0,000).Conclusion: Shows that counseling with animation video method can have a greater influence on the increase in preparedness